Intratumoral bacterial load and tertiary lymphoid structure density in hepatocellular carcinoma: association and prognostic significance - Qu, Shen; Jia, Weili; Liu, Xiaoyan; Yao, Qianyun; Chen, Chao; Zhao, Zihao; Nie, Ye; Chang, Feng; Yang, Zexu; Peng, Chaosheng; Wang, Yangang; Song, Wenjie (Frontiers in Immunology, 2025)
BackgroundThe tertiary lymphoid structures (TLS) within the immune microenvironment of hepatocellular carcinoma (HCC) have been shown to significantly influence patient prognosis. Understanding the mechanisms behind their formation and maturation can help us refine therapeutic strategies and improve treatment outcomes. In certain cancers, intratumoral bacteria have been found to promote the development of TLS. Our study aims to investigate the impact of intratumoral bacteria on TLS-associated immune cells in HCC, as well as their relationship with TLS quantity and maturation status.MethodsIn this study, we collected samples from 153 patients with hepatocellular carcinoma. We employed fluorescence in situ hybridization (FISH), immunofluorescence (IF), and hematoxylin and eosin (H&E) staining to assess intratumoral bacterial load, as well as to evaluate the number and maturation status of tertiary lymphoid structures. Patient prognosis was also analyzed. Furthermore, we examined the bacterial load and distribution within tumors of patients presenting TLS, and explored the relationship between intratumoral bacteria and TLS-associated immune cell infiltration.ResultsAmong 74 patients with hepatocellular carcinoma, tertiary lymphoid structures were present within the tumors. By integrating the expression profiles of both intratumoral and peritumoral TLS, prognostic analysis revealed that patients with structured tumor microenvironments (TME) and exclusionary TME had better outcomes. The intratumoral bacterial load varied among patients, with higher bacterial burden observed in regions enriched with TLS. Moreover, as TLS matured, the bacterial load within tumors was significantly greater compared to patients lacking TLS. Correspondingly, CD20, a major component of TLS, showed increased expression. These findings suggest that intratumoral bacteria can influence the immune response within the tumor microenvironment and are associated with the maturation of TLS.ConclusionOur study demonstrates that patients receiving structured TME and excluded TME subtypes exhibit superior overall survival (OS) and recurrence-free survival (RFS) following radical surgery. Furthermore, the intratumoral bacterial load showed a significant correlation with CD20+ B-cell density and was strongly correlated with both the number and maturity of TLS. These findings suggest that intratumoral bacteria may influence patient responses to immunotherapy.